Remission and Relapse in Alcohol and Substance Addiction - Alkin Yilmaz (Psikiyatride Guncel Yaklasimlar, 2014)
Alcohol and substance addiction is a chronic disease and continues throughout individual's life once after addiction develops. Therefore its natural course is characterized by remissions and relapses. In addiction, relapse periods can be followed by remission periods and individuals encounter with negative effects of alcohol and substances in these relapse periods. Many factors have been defined to determine the risk of relapse up to the date. These factors can be situational or personal and they also have physiological bases. Interaction of these factors with each other is critical in terms of relapse. Relapse is a quite well studied area in the literature, in order to prevent the individuals from restarting alcohol and substance use again. Defining the challenges of addicted patients in remission periods and recurrent periods of relapse in detail will guide clinicians to determine treatment strategies in addiction and to prevent subsequent relapse periods. [Psikiyatride Guncel Yaklasimlar - Current Approaches in Psychiatry 2014; 6(3.000): 243-256]